Investing in Agricultural Leadership for Sustainable Food Security Planning in Kenya: Historical Insights from Josephonomics - Waswa, Fuchaka (Machakos University, 2018)
Food insecurity and its indignity is still a persistent challenge in Kenya more than 50 years after independence. This paper opines that despite the country’s status of water scarcity with only about 30% of land being arable; Kenya can be food secure by tapping into already proven technological innovations in the agricultural sector. What is lacking or deficient is people-centred agricultural leadership that would tap into available and practical innovations without having to re-inventthe wheel and harness them into desired goods and services. Leadership in this context means ability to inspire people to deliver on their competences under their unique circumstances. This paper explores this dimension through lessons directly and indirectly derived from Josephonomics. This philosophy is based on how legendry Joseph saved ancient Egypt and the known world then from drought-driven starvation. Data was thus largely wed-based and secondary in nature. Content analysis informed the narrative that was designed to point out agricultural leadership innovations that this nation urgently needs. This paper has tapped into these lessons and applied them along the entire agricultural value chain. It is hoped that the lessons discussed can be utilised at both National and County government levels to create agricultural food belts and food stocks that would eliminate food insecurity and its impacts on households at much less budgetary implications contrary to what high cost complex research has been unable to deliver to date.
Keywords: Food Insecurity; Agricultural Leadership Innovations